Basis Pengembangan Kawasan Sapi Potong Berdasarkan Luas Tanaman Perkebunan dan Tanaman Pangan di Kabupeten Muna - Hidayat Hidayat; Muhammad Amrullah Pagala; Deki Zulkarnain (Universitas Halu Oleo, 2020)
This study aims to determine the potential development of beef cattle in Muna Regency by looking at the potential in several districts, which are the centers of beef cattle development. Parameters supporting the development of the area in the Muna Regency are the availability of grazing land and the availability of forage. The method of data collection uses a survey method through sampling in each predetermined area, then mapping the areas that have the potential for the development of forage in the area of plantations and food crops. The results of this study were obtained that the Districts of Muna Regency as the development of beef cattle-based estate crops and food crops.Keywords: area development; beef cattle; land resources